URGENSITAS PENYELESAIAN SENGKETA STATUS ANAK: KAJIAN PERKARA No. 49/Pdt.P/2020/PA.Pnj - Sofiana, Neng Eri (Al-IHKAM Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2022)
The status of the child is an important matter that must be resolved. In Case No. 49/Pdt.P/2020/PA.Pnj is a case of the origin of the fallen child. This paper will look at how the case can be dropped and how it affects the child whose origin is proposed. This paper will be carried out using library research methods and descriptive analysis as the analytical model used. As a result, this case was dropped due to the absence of the parties after being properly summoned for two summons. This certainly has an impact on the unclear status of the child, so that the child becomes a victim who bears the impact of the case that falls. There are many submissions for dispute resolution on the status of children because one of them is the number of sirri marriages.